The film club - Gilmour, David, 1949- (New York : Twelve, 2008)
Documents the author's efforts to impart key life lessons to his high-school-dropout son by showing him three movies every week, in an account that describes how such films as True Romance and Rosemary's
Filmography: p. [221]-225.
Keywords: Gilmour, David, 1949-; Gilmour, Jesse; Fathers and sons. -- Biogaphy; High school dropouts. -- Biography; Motion pictures and teenagers. -- Biography